The Secret Chicken Society - Cox, Judy.; Haley, Amanda (New York : Holiday House, 2012)
When Daniel's third-grade class raises baby chicks for a class project and he takes the five chickens home for the summer, he is surprised when one of them turns out to be a rooster.
Keywords: Chickens -- Fiction; Roosters -- Fiction; Family life -- Fiction